GENERACIÓN in vitro DE CÉLULAS DENDRÍTICAS HUMANAS DE ORIGEN MIELOIDE - Cuéllar Ávila, Adriana; Grupo de Inmunobiología y Biología Celular, Departamento de Microbiología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (Pontificia Universidad Javeriana, 2004)
Dendritic cell activity is an important step to elicit cellular immunity. These cells are the most potent antigen presenting cells and the main activating factor for naive T cells. There are several phenotypes of dendritic cells originated from different cell precursors. The aim of this study was to assess a model to obtain human myeloid dendritic cells from peripheral blood CD14+ monocytes. Cells were cultured in the presence of  granulocyte-monocyte colonies stimulating factor (GM-CSF) and IL-4 to obtain immature dendritic cells, wich were further cultured with PGE2 plus TNFa to induce their maturation. We obtained immature dendritic cells at  day 5 and mature dendritic cells at day 7, according to microscopic cellularphenotype and positivity of membrane markers for CD14, CD86, HLA-DR and CD83,